Peningkatan Kapasitas Produksi Bata Merah Melalui Penggunaan Mesin Cetak Bata Merah Model Extruder - Dwi Sahidin; Nugroho Tri Atmoko; Septi Purwaningsih; Tri Widodo Besar Riyadi; Margono Margono; Early Yanuar Ayuningtyas; Refly Yuliana (Politeknik Negeri Cilacap, 2026)
This Community Service Program aims to enhance the production capacity of red bricks at UMKM Putra Mandiri, located in Mulyadadi Village, Cipari District, Cilacap Regency, through the implementation of a red brick extruder machine. The partner’s main issue was the manual production process, which limited production capacity and resulted in inconsistent brick quality. The program activities included field observations, partner discussions, training sessions, and mentoring on machine operation and maintenance. The results showed that using the extruder machine significantly increased production capacity from 100 pcs/hour to 750 pcs/hour, indicating a 750% improvement compared to manual methods. Furthermore, the produced bricks demonstrated better uniformity, density, and strength, while reducing production time and labor intensity. The adoption of this appropriate technology not only improved productivity and competitiveness but also strengthened the partner’s independence in business operations. The implication of this activity is that technological transfer through community service programs can provide sustainable impacts on local economic development by promoting innovation, efficiency, and self-reliance among small enterprises.